Upacara Adat Basaru’ Sumangat dalam Konteks Batalah Tradisi Dayak Kanayatn dan Hubungannya dengan Liturgi Gerejani dalam Konteks Sakramen Pembaptisan - Amadi Amadi (VOCAT: JURNAL PENDIDIKAN KATOLIK, 2021)
This research aims to find out the basic meaning of the traditional ritual of Basaru 'sumangat in the context of batalah for Dayak Kanayatn people, the meaning of baptized sacrament in the Catholic Church, the relationship between Adat basaru' sumangat in the context of Batalah Kanayatn traditions with baptized sacrament Catholic Church. Using a qualitative approach, data were obtained from the results of in-depth interviews which focused on the village of Nangka, Landak district. The results of the research analysis show that: First, the basic meaning of the Batalah tradition of the Kanayatn Dayak people in Nangka Village is a ceremony that allows a newborn to gain safety. According to Kanayat Dayak belief in Nangka Village by carrying out the batalah ceremony, all bad things in the baby's body are removed thanks to the prayers delivered by the panyangahatn priest to Jubata or God, and by carrying out this batalah ceremony the existence of a baby will be recognized in society. Second, the meaning of the batalah tradition is almost the same as the tradition of the baptismal ceremony in the Catholic Church, which focuses on the appreciation of union with Jesus Christ which leads to holiness and salvation. Third, the relationship between the basaru 'sumangat ceremony in the context of the Batalah Dayak Kanayatn tradition with the sacrament ceremony of baptism in the Catholic Church is the path of holiness to salvation and the initiation of salvation. The path of holiness to salvation means that the holiness received through baptism or through the bat ceremony brings a person to salvation. Whereas the initiation of salvation is intended as a process that initiates a person into belonging to those who have safety. Both as members of the community (in babies who are questioned) and as members of the Church (in people who are baptized).